Robotic versus Laparoscopic Retroperitoneal Lymph node Dissection for Clinical Stage I Non-seminomatous Germ Cell Tumor of Testis: A Comparative Analysis - Xu, Yansheng; Li, Hongzhao; Wang, Baojun; Gu, Liangyou; Gao, Yu; Fan, Yang; Yao, Yuanxin; Fam, XengInn; Ma, Xin; Zhang, Xu (Urology Journal, 2021)
Purpose: To compare the treatment outcomes of robotic retroperitoneal lymph node dissection (R-RPLND) versus laparoscopic RPLND (L-RPLND) for clinical stage I non-seminomatous germ cell testicular tumors (NSGCTs). Materials and Methods: We retrospectively reviewed the data of patients with stage I NSGCTs who underwent robotic or laparoscopic RPLND between 2008 and 2017. Perioperative data and oncologic outcomes were reviewed and compared between the two groups. Progression-free survival was analyzed using Kaplan-Meier survival curves and compared between two groups. Results: A total of 31 and 28 patients underwent R-RPLND and L-RPLND respectively. The preoperative characteristics of the patients were comparable in the two groups. Patients in R-RPLND group had significantly shorter median operative time (140 vs. 175 minutes, P < .001), a shorter median duration to surgical drain removal (2 vs. 4 days, P = .002) and a shorter median postoperative hospital stay (5 vs. 6 days, P = .001). There were no statistical differences in intra- and post-operative complication rate between the groups and the oncologic outcomes were similar in the two groups. Conclusion: In expert hands, R-RPLND and L-RPLND were comparable in oncological parameter and morbidity rate; R-RPLND showed superiority in operation duration, median days to surgical drain removal and postoperative hospital stay for stage I NSGCTs. Multicenter and randomized studies with good power of study and sufficient follow-up duration are required to validate our result.